Association of Hypertension on Development of Coronary Collaterals in Severe Coronary Artery Disease - Hossain, Solaiman; Majumder, Abdullah Al Shafi; Ullah, Mohammad; Shaha, Chandan Kumar; Mannan, Md Abdul (Cardiovascular Journal, 2015)
Objectives: Coronary collaterals appear to play important role in coronary artery disease morbidity and mortality. In this study it was intended to determine whether hypertension is associated with development of coronary collaterals in patients with severe coronary artery disease. Methods: This was an observational cross-sectional study carried out in the department of cardiology of National Institute of Cardiovascular Diseases, Dhaka, Bangladesh during the period from October 2010 to June 2011. A total of 334 patients were examined to include in the study. Among them 118 patient of severe coronary artery disease (CAD) were included who fulfilled the inclusion and exclusion criteria. From where 63 patients were CAD with hypertension (Group -I) and 55 patients were CAD without hypertension (Group -II). Based on Rentrop Grading the study patients were divided in two groups, patients with poor collaterals (Grade 0& 1) and good collaterals (Grade 2&3). Data compared the coronary collaterals in hypertensive patients with those without hypertension with severe coronary artery disease. Results: The data showed that good collateral circulations were higher with duration of hypertension. The difference were statistically significant in duration <5 years and duration >10 years in both groups (p<0.05). The pattern of vessel involvement in double vessel disease and triple vessel disease (p <.001) and dyslipidemia (p<0.004) appeared to be significant predictor of hypertension controlling for other factors in the model. People with hypertension are around four times more likely to have good collateral circulation, multiple vessel disease and around 12 times more likely to have dyslipidemia. Conclusion: It is concluded that the patients of hypertension develop higher grades of coronary collaterals which increases with duration of hypertension in patients of severe coronary artery disease. Involvements of coronary arteries were more extensive in patients of hypertension with coronary artery disease. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22250 Cardiovasc. j. 2015; 7(2): 98-103